DJ‐1 inhibits autophagy activity of prostate cancer cells by repressing JNK–Bcl2–Beclin1 signaling. (5th January 2020) - Qin, Xiangcheng; Lu, Aimei; Ke, Meilin; Zhu, Weizhi; Ye, Xiaolei; Wang, Gang; Weng, Guobin
Abstract: The regulation of DJ‐1 on AR signaling plays an important role in the pathogenesis of prostate cancer (PCa). DJ‐1 could alter autophagy and regulate Beclin1‐involved autophagy response through JNK‐dependent pathway. JNK is known to mediate autophagy through Bcl2–Beclin1 complex. Therefore, this study aimed to investigate the significance of autophagy in DJ‐1‐modulated PCa cells. The current studies showed that DJ‐1 overexpression in LNCaP decreased LC3 transformation and autophagosome formation. However, DJ‐1 knockdown exerted the opposite effect. Moreover, DJ‐1 silencing inhibited survival and promoted death in LNCaP, which was recovered by autophagy inhibition with 3‐MA. In addition, DJ‐1 overexpression inhibited the phosphorylation of JNK and Bcl2, and the dissociation of Beclin1 and Bcl2; while the effect of silencing DJ‐1 was completely opposite. More important, JNK activated by anisimycin inhibited the proliferation and promoted death of DJ‐1‐overexpressed LNCaP while increasing LC3 transformation and LC3‐puncta formation, but these results were reversed by the decrease of Beclin1 (by spautin‐1). In contrast, when DJ‐1 was silenced, the death of LNCaP, LC3 transformation, and LC3‐puncta formation were inhibited by JNK inhibitor SP600125, which promoted cell proliferation. However, Bcl2 inhibition (by ABT737) reversed all the effects of SP600125. Our results suggested that DJ‐1 in PCa cells could promote the growth of PCa through autophagy inhibition, and JNK–Bcl2–Beclin1 signaling played an important role in it. The study provided new insights into the role of DJ‐1 in the development of PCa.